Brusatol has therapeutic efficacy in non-small cell lung cancer by targeting Skp1 to inhibit cancer growth and metastasis. (February 2022) - Xing, Shangping; Nong, Feifei; Wang, Yaqin; Huang, Da; Qin, Jialiang; Chen, Yu-Fei; He, Dan-Hua; Wu, Pei-En; Huang, Huicai; Zhan, Ruoting; Xu, Hui; Liu, Yong-Qiang
Abstract: Skp1-Cul1-F-box protein (SCF) ubiquitin E3 ligases play important roles in cancer development and serve as a promising therapeutic target in cancer therapy. Brusatol (Bru), a known Nrf2 inhibitor, holds promise for treating a wide range of tumors; however, the direct targets of Bru and its anticancer mode of action remain unclear. In our study, 793 Bru-binding candidate proteins were identified by using a biotin-brusatol conjugate (Bio-Bru) followed by streptavidin-affinity pull down-based mass spectrometry. We found that Bru can directly bind to Skp1 and disrupt the interactions of Skp1 with the F-box protein Skp2, leading to the inhibition of the Skp2-SCF E3 ligase. Bru inhibited both proliferation and migration via promoting the accumulation of the substrates p27 and E-cadherin; Skp1 overexpression attenuated while Skp1 knockdown enhanced these effects of Bru in non-small cell lung cancer (NSCLC) cells. Moreover, Bru binding to Skp1 also inhibited the β-TRCP-SCF E3 ligase. In both subcutaneous and orthotopic NSCLC xenografts, Bru significantly inhibited the growth and metastasis of NSCLC through targeting SCF complex and upregulating p27 and E-cadherin protein levels. These data demonstrate that Bru is a Skp1-targeting agent that may have therapeutic potentials in lung cancer. Graphical Abstract: ga1 Highlights: Biotin-brusatol conjugate and mass spectrometry were employed to identify that brusatol can target Skp1, an adaptor protein of SCF E3 ligase. Brusatol binding to Skp1 leads to the inhibition of SCF E3 ligase such as Skp2-SCF E3 ligase, leading to the accumulation of E-cadherin and p27. Brusatol at low concentrations (1–2 mg/kg) inhibits proliferation and metastasis of NSCLC xenografts via inhibiting SCF E3 ligase.